Depression Affects Intrinsic Brain Activity in Patients With Mild Cognitive Impairment - Yu, Yang; Li, Ziqi; Lin, Yajie; Yu, Jie; Peng, Guoping; Zhang, Kan; Jia, Xize; Luo, Benyan (Frontiers in Neuroscience, 2019)
Numerous observational studies have shown that depressive symptoms are common in individuals with mild cognitive impairment (MCI) who have a higher progression rate to dementia. However, it is currently unclear whether the brain function activity in MCI patients with depression symptom differs from those without depression symptom. The aim of this study is to identify the brain function activity differences in two groups of MCI patients (with depression or without depression) by using the dynamic measurements, and assessed the correlation between the brain function and clinical depressive symptom. The present study utilized sliding window approaches to capture the dynamic characteristics of regional brain activity. A total of 76 right-handed MCI subjects were recruited in the study, including 27 patients combined with depression symptoms (MCID), 49 MCI without depression patients (MCIND). Analyses included both three static measurements (ALFF, fALFF and ReHo) and three dynamic measurements (dALFF, dfALFF and dReHo) to investigate the temporal variability of brain activity. We found that in MCID, dfALFF decreased in cuneus, occipital gyrus and calcarine. Also, fALFF in MCID group decreased in temporal gyrus, frontal gyrus, inferior occipital gyrus, middle frontal gyrus and cerebellum, but increased in cuneus, calcarine, lingual. Compared to MCIND group, MCID group exhibited obvious increase dReHo in bilateral MTG, ITG, superior temporal gyrus (STG), superior parietal lobule, inferior parietal gyrus (IPG), precuneus, superior frontal gyrus (SFG), middle frontal gyrus (MFG), inferior frontal gyrus (IFG). However, we only found ReHo in cerebellum differs between the two groups. Moreover, dfALFF in cuneus was found a negative correlation with Geriatric Depression Scale (GDS) score, while dReHo in SFG, IFG, MTG and ITG were found a positive correlation with GDS score. These may provide a better understanding of the relationship between depressive symptoms and memory deficits.